Semarang 1652-1741: Para Bupatinya di Bawah Kuasa Mataram dan VOC, by Iqbal Rizaldin, Surabaya, Pustaka Indis, 2024, 264 pp., IDR 90.000 (paperback), ISBN 9786235618777 - Mukhammad Nur Rokhim (Abjad Journal of Humanities & Education, 2026)
Semarang, the capital of Central Java Province, has been one of the region’s significant economic centres since ancient times. During the classical period, the Port of Bergota served as one of the gateways for transnational trade under the control of Mataram (Rukayah et al., 2023; Rukayah et al., 2022; Yuliati et al., 2023; Yuliati & Susilowati, 2023). The city also played an important role in Demak’s political constellation, functioning as both a maritime and military agglomeration zone (Pigeaud, 1970). As a port city, Semarang became a coveted territory for parties seeking various forms of profit. Ki Ageng Made Pandan, the first regent of Semarang, was still related to Raden Patah. As the political centre shifted to Pajang and later Mataram, the descendants of Ki Ageng Made Pandan continued to serve as respected regents. However, this economic region experienced turbulence as a result of political dynamics following the decline of Sultan Agung Hanyakrakusuma’s power and the succession of the throne by Amangkurat I, who also entered into economic and political compromises with the VOC.